![image](https://tex.z-dn.net/?f=y%20%2B%202%20%3E%20x%20%5Cdiv%20x%20-%201%20%5C%5C%20%7Bx%7D%5E%7B2%7D%20-%202x%20%2B%20y%20%3C%203%20%5C%5C%20y%20%2B%202%20%3E%201%20-%201%20%5C%5C%20y%20%3E%20-%202%20%5C%5C%20%7Bx%7D%5E%7B2%7D%20-%202x%20-%202%20%3C%203%20%5C%5C%20%7Bx%7D%5E%7B2%7D%20-%202x%20-5%20%3C%200%20%5C%5C%20d%20%3D%20-%204%20-%204%20%5Ctimes%20-%205%20%3D%20-%204%20%2B%2020%20%3D%2016%20%5C%5C%20%5Csqrt%7B16%7D%20%3D%204%20%5C%5C%20x1%20%3D%20%5Cfrac%7B2%20%2B%204%7D%7B2%7D%20%3D%20%5Cfrac%7B6%7D%7B2%7D%20%3D%203%20%5C%5C%20x2%20%3D%20%5Cfrac%7B2%20-%204%7D%7B2%7D%20%3D%20-%201%20%5C%5C%20x%20%3C%203%20%5C%5Cy%20%3E%20-%202)
x \div x - 1 \\ {x}^{2} - 2x + y < 3 \\ y + 2 > 1 - 1 \\ y > - 2 \\ {x}^{2} - 2x - 2 < 3 \\ {x}^{2} - 2x -5 < 0 \\ d = - 4 - 4 \times - 5 = - 4 + 20 = 16 \\ \sqrt{16} = 4 \\ x1 = \frac{2 + 4}{2} = \frac{6}{2} = 3 \\ x2 = \frac{2 - 4}{2} = - 1 \\ x < 3 \\y > - 2" alt="y + 2 > x \div x - 1 \\ {x}^{2} - 2x + y < 3 \\ y + 2 > 1 - 1 \\ y > - 2 \\ {x}^{2} - 2x - 2 < 3 \\ {x}^{2} - 2x -5 < 0 \\ d = - 4 - 4 \times - 5 = - 4 + 20 = 16 \\ \sqrt{16} = 4 \\ x1 = \frac{2 + 4}{2} = \frac{6}{2} = 3 \\ x2 = \frac{2 - 4}{2} = - 1 \\ x < 3 \\y > - 2" align="absmiddle" class="latex-formula">
x≠-1